Didactic Focus Areas in Science Education Research - Jarkko Lampiselkä; Arja Kaasinen; Päivi Kinnunen; Lauri Malmi (MDPI AG, 2019)
This study provides an overview of the didactic focus areas in educational research in biology, chemistry and physics, seeking to identify the focus areas that are investigated frequently and those that have been studied rarely or not at all. We applied the didactic focus-based categorization analysis method (DFCM), which is based on an extension of the didactic triangle. As the data set, we used 250 papers published in the Nordic Studies in Science Education (NorDiNa) between 2005 and 2013, and the European Science Education Research Association (ESERA) 2013 conference proceedings covering education at upper secondary and tertiary levels. The results show that the teacher's pedagogical actions and the student-content relationship were the most frequently studied aspects. On the other hand, teachers' reflections on the students' perceptions and attitudes about goals and content, and teachers' conceptions of the students' actions towards achieving the goals were studied least. Irrespective of the publication forum, the distributions of foci to different categories were quite similar. Our historical analysis completes the recent studies in the field as it is based on the theory driven categorization system instead of the data driven approaches used by the previous researchers. Moreover, our further observations on more recent publications suggest that no significant changes have taken place, and therefore wider discussion about the scope and the coverage of the research in science education is needed.